2016
DOI: 10.1590/1413-81232015214.13672015
|View full text |Cite
|
Sign up to set email alerts
|

Edentulism in Brazil: trends, projections and expectations until 2040

Abstract: The aim of this study was to examine the edentulism rates in Brazil and make projections for the next years. Data were collected from three national oral health surveys. The percentage of edentulous jaws was calculated. Projections were made for the years 2020, 2030 and 2040, assuming that edentulism follows a logistic function. Population projections were also performed. Annual change in proportion of edentulous jaws was -0.04% for teenagers, -0.96% for adults and 0.76% for the elderly. By 2040, edentulous ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
26

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 12 publications
1
39
0
26
Order By: Relevance
“…Turning to the findings, a cumulative incidence of 11% over the eight-year period is higher than the age-standardized incidence of severe tooth loss in 2010 in Brazil (440 per 100 000 person-years) and the global age-standardized incidence rate of <0.001 5-minute stimulated saliva flowmean (AESD) 4.0 (AE2.8) 3.1 (AE1.9) <0.001 Gingival Bleeding Indexmean (AESD) 50,2 (AE26.3) 79,4 (AE30.9) 0.04 severe tooth loss in 2010, which was 205 cases per 100 000 person-years 32 . This result is also in line with evidence from time-series studies showing a decline in the prevalence of edentulism in some countries in Europe 33 , New Zealand 5 and the United States 34 , whereas in Brazil, it has increased over the last two decades among older adults 9 .…”
Section: Discussionsupporting
confidence: 89%
“…Turning to the findings, a cumulative incidence of 11% over the eight-year period is higher than the age-standardized incidence of severe tooth loss in 2010 in Brazil (440 per 100 000 person-years) and the global age-standardized incidence rate of <0.001 5-minute stimulated saliva flowmean (AESD) 4.0 (AE2.8) 3.1 (AE1.9) <0.001 Gingival Bleeding Indexmean (AESD) 50,2 (AE26.3) 79,4 (AE30.9) 0.04 severe tooth loss in 2010, which was 205 cases per 100 000 person-years 32 . This result is also in line with evidence from time-series studies showing a decline in the prevalence of edentulism in some countries in Europe 33 , New Zealand 5 and the United States 34 , whereas in Brazil, it has increased over the last two decades among older adults 9 .…”
Section: Discussionsupporting
confidence: 89%
“…Despite the above shortcomings, these two studies suggested a contralateral symmetry in the clinical and radiographic parameters of subjects with chronic periodontitis, and the average subject age was 47.5 and 55.5 years, respectively. However, inclusion of older subjects would have been a study limitation, as tooth loss increases with age, and this specific sample population has a high prevalence of tooth loss (29). One of the inclusion criteria of this study was the presence of at least 20 teeth, and this would have limited the sample size as well as the age of patients in the chronic periodontitis group.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, a OMS encoraja a investigação de fatores de risco e o impacto da perda dentária nos idosos, a fim de gerir a intervenção e programas assistências 23 . A ampliação do acesso ao serviço de prótese dentária no Sistema Único de Saúde é uma necessidade real e de grande demanda 24 , devendo-se priorizar o atendimento das populações, cujos parâmetros dos níveis sociodemográficos influenciam na utilização ou necessidade de próteses, conforme demonstrado no estudo, pois segundo Cardoso et al 25 , o edentulismo está diminuindo no Brasil entre jovens e adultos, mas está aumentando e continuará a aumentar nas próximas décadas entre os idosos.…”
Section: Gênerounclassified